Sex differences in acetylcholinesterase modulation during spatial and fear memory extinction in the amygdala; an animal study in the single prolonged stress model of PTSD - Ahmad Mohammadi-Farani; Sajad Farhangian; Samira Shirooie (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Men and women show different reactions to trauma and that is believed to be the reason behind the higher prevalence of post-traumatic stress disorder (PTSD) in women. Cholinergic signaling has long been known to be involved in the processing of fear-related information and the amygdala is a critical center for fear modulation. The main goal of the current research was to find (a) whether trauma results in different learning/extinction of fear or spatial-related information among male and female rats and (b) if trauma is associated with different acetylcholinesterase (AchE) activity in the amygdala. Experimental approach: We used single prolonged stress (SPS) as a PTSD model in this study. Normal and SPS animals of both sexes were tested in contextual and spatial tasks (learning and extinction). AchE activity in the amygdala was also measured during each process. Findings / Results: Results indicated that fear and spatial learning were impaired in SPS animals. SPS animals also had deficits in fear and spatial memory extinction and the effect was significantly higher in female- SPS than in the male-SPS group. In the enzymatic tests, AchE activity was increased during the fear extinction test and incremental changes were more significant in the female-SPS group. Conclusion and implications: Collectively, these findings provided evidence that sex differences in response to trauma were at least partly related to less fear extinction potential in female subjects. It also indicated that the extinction deficit was associated with reduced cholinergic activity in the amygdala of female animals.